4D flow MRI quantification of mitral and tricuspid regurgitation: Reproducibility and consistency relative to conventional MRI. Issue 4 (11th April 2018) - Feneis, Jennifer F.; Kyubwa, Espoir; Atianzar, Kimberly; Cheng, Joseph Y.; Alley, Marcus T.; Vasanawala, Shreyas S.; Demaria, Anthony N.; Hsiao, Albert
Abstract : Background: In patients with mitral or tricuspid valve regurgitation, evaluation of regurgitant severity is essential for determining the need for surgery. While transthoracic echocardiography is widely accessible, it has limited reproducibility for grading inlet valve regurgitation. Multiplanar cardiac MRI is the quantitative standard but requires specialized local expertise, and is thus not widely available. Volumetric 4D flow MRI has potential for quantitatively grading the severity of inlet valve regurgitation in adult patients. Purpose: To evaluate the accuracy and reproducibility of volumetric 4D flow MRI for quantification of inlet valvular regurgitation compared to conventional multiplanar MRI, which may simplify and improve accessibility of cardiac MRI. Study Type: This retrospective, HIPAA‐compliant imaging‐based comparison study was conducted at a single institution. Subjects: Twenty‐one patients who underwent concurrent multiplanar and 4D flow cardiac MRI between April 2015 and January 2017. Field Strength/Sequences: 3T; steady‐state free‐precession (SSFP), 2D phase contrast (2D‐PC), and postcontrast 4D flow. Assessment: We evaluated the intertechnique (4D flow vs. 2D‐PC), intermethod ( direct vs. indirect measurement), interobserver and intraobserver reproducibility of measurements of regurgitant flow volume (RFV), fraction (RF), and volume (RVol). Statistical Tests: Statistical analysis included Pearson correlation, Bland–Altman statistics, and intraclass correlation coefficients. Results: There was high concordance between 4D flow and multiplanar MRI, whether using direct or indirect methods of quantifying regurgitation ( r = 0.813–0.985). Direct interrogation of the regurgitant jet with 4D flow showed high intraobserver consistency ( r = 0.976–0.999) and interobserver consistency ( r = 0.861–0.992), and correlated well with traditional indirect measurements obtained as the difference between stroke volume and forward outlet valve flow. Data Conclusion: 4D flow MRI provides highly reproducible measurements of mitral and tricuspid regurgitant volume, and may be used in place of conventional multiplanar MRI. Level of Evidence : 4 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2018;48:1147–1158.